Lots and Lots of Coins - Reid, Margaretts S.; Kelley, True (New York : Dutton Children's Books, 2011)
A father and son discover the value of coins, what people used before coins, and why historical images and people appear on coins.
Keywords: Coins -- Collectors and collecting; Coins